(untitled) (Nepalese Medical Journal, 2018)
In a country like Nepal; where leprosy is prevalent, when a patient comes to us with nodular lesions, the first diagnosis is leprosy. A case of sarcoidosis with cutaneous and pulmonary involvement is reported here. In this patient initially the diagnosis of Hansen disease was made and was treated accordingly. As there was no improvement, a clinical suspicion of sarcoidosis. Presence of non-caseating granuloma in histopathology report and findings in chest X-Ray helped to reach in the diagnosis of sarcoidosis and was treated accordingly after which the patient showed significant clinical improvement. This case is presented here to emphasize that though in our part of the world and cutaneous sarcoidosis is rare; Sarcoidosis should be kept as one of the differential diagnosis, if clinically suspicious. Nepalese Medical Journal, vol.1, No. 1, 2018, Page : 51-53